Enhanced perceptual priming for neutral stimuli in a traumatic context: A pathway to intrusive memories? - Ehlers, A; Michael, T; Chen, Y; Payne, E; Shan, S (2006)
Clinical observations suggest that re-experiencing symptoms are triggered by stimuli that are perceptually similar to those present shortly before the trauma or its worst moments. Two experiments investigated the possible role of perceptual priming in this phenomenon. Volunteers (N = 28, N = 62) watched a series of "traumatic" and neutral picture stories, and completed blurred object identification (priming) and recognition memory tasks. Neutral objects that immediately preceded the "traumatic" stories were more strongly primed, but not better recognised, than objects from neutral stories. Enhanced priming predicted subsequent re-experiencing symptoms. The results support the role of perceptual priming in re-experiencing.